Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.heliyon.2021.e07083
|View full text |Cite
|
Sign up to set email alerts
|

Cerebroprotective effect of pterostilbene against global cerebral ischemia in rats

Abstract: The role of pterostilbene against induced neurobehavioral alterations in global cerebral ischemiareperfusion and oxidative damage was studied. Materials and methods: Male SD rats (180-200 g) were exposed for 30 min to bilateral carotid artery occlusion accompanied by 60 min reperfusion to cause cerebral injury. Pretreatment with pterostilbene (200 and 400 mg/ kg, orally) was given to the animals for ten days followed by ischemia-reperfusion injury. Various behavioral tests (locomotor activity, neurological sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…It was found that after ischemic stroke, intracranial perfusion was reduced, SOD, GSH, and CAT levels decreased, and lipid peroxidation (LPO) levels, a measure of the severity of oxidative damage to brain tissue, increased, all of which were significantly reversed and returned to near-healthy levels in a group pretreated with pterostilbene. Pterostilbene treatment also inhibited the production of ROS, acting as a free radical scavenger and protecting neurons, demonstrating the therapeutic potential of pterostilbene for cerebral ischemia–reperfusion injury . In addition, pterostilbene can also inhibit oxidative stress by regulating a number of pathways.…”
Section: Pharmacological Effects Of Pterostilbene: Evidence From In V...mentioning
confidence: 90%
See 1 more Smart Citation
“…It was found that after ischemic stroke, intracranial perfusion was reduced, SOD, GSH, and CAT levels decreased, and lipid peroxidation (LPO) levels, a measure of the severity of oxidative damage to brain tissue, increased, all of which were significantly reversed and returned to near-healthy levels in a group pretreated with pterostilbene. Pterostilbene treatment also inhibited the production of ROS, acting as a free radical scavenger and protecting neurons, demonstrating the therapeutic potential of pterostilbene for cerebral ischemia–reperfusion injury . In addition, pterostilbene can also inhibit oxidative stress by regulating a number of pathways.…”
Section: Pharmacological Effects Of Pterostilbene: Evidence From In V...mentioning
confidence: 90%
“…Pterostilbene treatment also inhibited the production of ROS, acting as a free radical scavenger and protecting neurons, demonstrating the therapeutic potential of pterostilbene for cerebral ischemia− reperfusion injury. 107 In addition, pterostilbene can also inhibit oxidative stress by regulating a number of pathways. The Nrf2/ HO-1 pathway is a major regulatory pathway for intracellular antioxidant defense.…”
Section: Strokementioning
confidence: 99%
“…Our previous study found that PT improved the quality of chicken breast meat through enhancing the antioxidant enzymes expression related to Nrf2 pathway and reducing lipid and protein oxidation. In the therapy of reperfusion‐induced ischaemia rats, PT showed the free radical scavenging property by increasing the activities of CAT and GSH (Khan et al, 2021). PT was reported to alleviate diquat‐induced jejunum damage of chicken via regulating redox status mediated by Nrf2 and ferroptosis (Chen et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies have revealed Pte’s antioxidant, anti-apoptotic, anticancer, and anti-inflammatory properties [ 27 ], making Pte a potential therapeutic agent for treating various diseases, including IS. Badruddeen et al [ 28 ] found that Pte affected reperfuse-induced ischemia and related behavioral changes in rats. Owing to its antioxidant and free radical scavenging properties, and its ability to regulate neurodegenerative brain oxidative damage, Pte can be used as a neuroprotective adjuvant to effectively eradicate oxidative stress during in vivo ischemic injury [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%